Development of supplementary respiratory system teaching materials integrated with Islamic values in the formation of an attitude of caring about the dangers of smoking - Wiradani, Liviana Putri; Lisdiana, Lisdiana; Widyaningrum, Priyantini (Journal of Innovative Science Education, 2022)
SMA Al-I'tishom is a boarding school that applies two curricula, namely the national education curriculum and the pesantren curriculum. Seeing the condition of the school environment with the background of Islamic boarding schools and the absence of integrated teaching materials with Islamic values. This study aims to develop a supplementary respiratory system teaching material that integrates Islamic values ​​in the formation of an attitude of caring about the dangers of smoking. This development research refers to the ADDIE development model which consists of the Analysis, Design, Development, Implementation, and Evaluate. The test of the validity of the teaching material supplements was carried out by three biology learning experts as validators. The practicality test is carried out through learning in class XI science high school students. Test the effectiveness of teaching material supplements through a pre-experiment with a one-shot-case-styudy design. The test results show that the average percentage score of the validity of the three validators is 88.33% with very valid criteria. The results of the practicality test obtained an average of 90.45% with very practical criteria. The results of the learning implementation trial obtained an average score of 89.50% with very practical criteria. The results of the trial of the attitude of caring about the dangers of smoking obtained an average score of 85%. Based on the results of the validity test, practicality test, and effectiveness test, the supplement of Islamic values ​​integrated respiratory system teaching materials produced through research can be declared valid, and can form an attitude of caring about the dangers of smoking.